2016
DOI: 10.1016/j.ijscr.2016.09.044
|View full text |Cite
|
Sign up to set email alerts
|

Liver Angiosarcoma: Rare tumour associated with a poor prognosis, literature review and case report

Abstract: HighlightsLiver Angiosarcoma is rare and aggressive tumour that requires surgical management.Partial Hepatectomy is the ideal surgical management for Liver Angiosarcoma.Liver transplant does not improve the survival of Liver Angiosarcoma patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
11
0
1

Year Published

2017
2017
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(13 citation statements)
references
References 12 publications
1
11
0
1
Order By: Relevance
“…On MRI, the tumors appear as a heterogeneous area, and hemorrhage is reflected by hyperintense spots or patchy signals on T1 and T2-weighted images. PET/CT scan has a major role in staging the tumor and detection of distant metastasis, appearing FDG-avid on PET-CT [ [17] , [18] , [19] ]. Cinematic rendering is a recently described 3-dimensional (3D) imaging technique that generates photorealistic images based on a new lighting model [ 20 ].…”
Section: Discussionmentioning
confidence: 99%
“…On MRI, the tumors appear as a heterogeneous area, and hemorrhage is reflected by hyperintense spots or patchy signals on T1 and T2-weighted images. PET/CT scan has a major role in staging the tumor and detection of distant metastasis, appearing FDG-avid on PET-CT [ [17] , [18] , [19] ]. Cinematic rendering is a recently described 3-dimensional (3D) imaging technique that generates photorealistic images based on a new lighting model [ 20 ].…”
Section: Discussionmentioning
confidence: 99%
“…While up to 75% of cases are of unknown aetiology, known risk factors for the development of hepatic angiosarcoma include the use of oral contraceptives, exposure to anabolic steroids, radiation, thorium dioxide, arsenic and vinyl chloride 4. There is also a link between the development of hepatic angiosarcoma in patients with neurofibromatosis type 1 and haemochromatosis 10.…”
Section: Discussionmentioning
confidence: 99%
“…Optimal management of patients is poorly demarcated due to the rarity of hepatic angiosarcoma 18. Most patients pass away within 2 years of diagnosis and have a median survival time of 6 months without treatment 4. Liver transplantation is contraindicated in patients with hepatic angiosarcoma due to a high recurrence rates and poor survival outcomes despite transplantation.…”
Section: Discussionmentioning
confidence: 99%
“…Unfortunately, only few studies have reported on the association of HAS with fatty liver. Millan et al [ 14 ] reported a case of HAS with a 7-year history of fatty liver. HAS with nonalcoholic steatohepatitis was also reported in Japan (unpubl.…”
Section: Discussionmentioning
confidence: 99%